Stimulation of muscle protein synthesis with low-dose amino acid composition in older individuals - Church, David D.; Ferrando, Arny A.; Wolfe, Robert R. (Frontiers in Nutrition, 2024)
Essential amino acid (EAA)-based compositions have been shown to be effective stimulators of muscle protein synthesis, but the lower limit of effective dosage is not clear. We have used stable isotope tracer methodology to quantify the response of muscle protein fractional synthetic rate (FSR) to a dose of 3.6 g of a high-leucine composition of EAAs plus arginine in older subjects. Muscle protein FSR increased 0.058 %/hour over three hours following consumption. When account was taken of the total muscle mass, this increase in muscle protein FSR represented approximately 80% of ingested EAAs. We conclude that a low dose of an EAA-based composition can effectively stimulate muscle protein synthesis.